Graduate student perspectives on online teaching of writing - Guadalupe Álvarez; Hilda Difabio de Anglat; Lourdes Morán (Universidad de Guadalajara, 2023)
The aim of this study is to characterize the graduate student perspectives on a virtual dialogic teaching initiative oriented to the revision of dissertation chapters written by the students themselves. Within an exploratory qualitative study in-depth interviews are taken with 12 students from three seminar editions. The analysis shows three relevant categories regarding online dialogic teaching of writing: time management, synchronous exchange and digital technologies. There are three senses of the temporal dimension: times relative to the seminar schedule, to the student daily life, and to the intellectual process of writing practices. Further-more, a combination of heavy asynchronous load with synchronous encounters is valued. Regarding the technologies, the students generate environments that take advantages of devices' technological potential based on the physical environment possibilities and also value the pedagogical relevance of the applications. The category properties show some changes of graduate writing, and its dialogic teaching in the digital world.